2013
DOI: 10.1088/0022-3727/46/13/133001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of biological specimens explored by atomic force microscopy

Abstract: The atomic force microscope is a widely used surface scanning apparatus capable of reconstructing at a nanometric scale resolution the 3D morphology of biological samples. Due to its unique sensitivity, it is now increasingly used as a force sensor, to characterize the mechanical properties of specimens with a similar lateral resolution. This unique capability has produced, in the last years, a vast increase in the number of groups that have exploited the versatility and sensitivity of the instrument to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 98 publications
1
74
0
2
Order By: Relevance
“…In summary, traditional AFM single-cell mechanical assays measure only the elastic properties (Young's modulus) of cells (Kasas et al, 2013), whereas the flow of cytoplasm of living cells in response to environmental or intrinsic cues is related to the longstanding and unsolved fundamental issues in cell mechanics (Moeendarbary et al, 2013;Zhou et al, 2013). Hence, quantifying the viscoelastic properties of cells can help us to better understand the underlying mechanisms of cell mechanics.…”
Section: Rusults and Discussionmentioning
confidence: 99%
“…In summary, traditional AFM single-cell mechanical assays measure only the elastic properties (Young's modulus) of cells (Kasas et al, 2013), whereas the flow of cytoplasm of living cells in response to environmental or intrinsic cues is related to the longstanding and unsolved fundamental issues in cell mechanics (Moeendarbary et al, 2013;Zhou et al, 2013). Hence, quantifying the viscoelastic properties of cells can help us to better understand the underlying mechanisms of cell mechanics.…”
Section: Rusults and Discussionmentioning
confidence: 99%
“…The indentation depth δ was computed by subtracting the cantilever deflection from the vertical movement of the probe according to the contact point visually determined in the force curve [10]. The approach curve was used to extract cellular instantaneous modulus [25], while the retract curve was used for calculating the adhesion forces between tip and cell. The software for extracting the instantaneous modulus from the force curves was programmed by ourselves using MATLAB.…”
Section: H Data Analysismentioning
confidence: 99%
“…Nevertheless, studies have shown that Hertz model is appropriate for measuring the elastic properties of cells as long as the indentation into the specimen is no more than 10% of the specimen thickness [27]. Hertz model does not consider the adhesion forces between contact surfaces, while Johnson-KendallRoberts (JKR) model and Derjaguin-Muller-Toporov (DMT) model take into account of the adhesion forces between the contact surfaces [25]. But for practical reasons, the most wildly used model is Hertz model [10].…”
Section: H Data Analysismentioning
confidence: 99%
“…A force curve contains two components: an approach curve and a retract curve. The approach curve is used to calculate the cellular Young's modulus [42] because the retract curve is often influenced by tip-sample adhesions, making it difficult to discern the contact point of the latter. By contrast, the contact point of the approach curve can be clearly visualized (denoted in Figure 1B).…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%
“…However, the indentations should be larger than 400 nm to avoid errors due to the uncertain determination of the contact point, which leads to measurements often being performed on the central region of the cell [47] . The Hertz-Sneddon model does not consider the forces between the contact surfaces (eg, electrostatic forces, adhesion forces and friction forces) [42] and is therefore applicable when the forces between the contact surfaces are negligible compared with the maximum load. By contrast, the JohnsonKendall-Roberts (JKR) model and Derjaguin-Muller-Toporov (DMT) model take into account the adhesion forces between the contact surfaces.…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%